To manage livestock farming system, which tools for which goals and which users? Examples from France - Benoît M.; Ingrand S. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
Farmers and their technical advisors use tools to manage livestock farming systems. Those tools are more or less complex and deal with decisions which can be either short term (tactical) or long term, having consequences on the system configuration (strategy). We present a sample of tools, used on the ground, particularly on sheep production, and based or not on a modeling process. They concern many domains, like feeding animals, managing the flock, work organization, range of animals to sell… We compare then those different tools, according to their goals, in relation with the users’ involvement during the designing process. This involvement seems to be crucial, especially for long term decision tools.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)